Kế hoạch hóa quản lý cán bộ bằng lý thuyết đổi mới - Lam, Lê Xuân (Journal of Computer Science and Cybernetics, 2016)
In this work we present an application of the renewal theory to the administrative affair of the state cadre. The algorithm to predict and to solve optimization problems occurred in our theory is developed. These algorithms are written in Turbo Pascal V.5 for IBM PC AT and are illustrated by the numerical example.